Model Storytelling Untuk Meningkatkan Ketrampilan Menyimak Dongeng Siswa Kelas III Sekolah Dasar - Sri Mardiyanti; Sumarno Sumarno; Ida Wijayanti (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the use of the storytelling method in improving the listening skills of class III students. The storytelling method was chosen because it can stimulate students' imagination and creativity, and help them understand and capture stories better. This study uses a qualitative approach. The research subjects consisted of 46 grade III students from 3 elementary schools. The research was conducted in three cycles, where each cycle consisted of planning, implementing, observing, and reflecting. The storytelling method is applied in each research cycle. Teachers use various storytelling techniques, such as the use of sound, movement, and visualization, to convey fairy tales to students. After each storytelling session, students are asked to do listening activities, such as answering questions about the story, retelling the story in their own words, or drawing story scenes. The results showed that the use of the storytelling method significantly improved the listening skills of grade III students. This improvement can be seen from significant changes in students' ability to understand stories, remember important details, and express their understanding orally and in writing. This study provides evidence that the storytelling method is effective in improving the listening skills of grade III students. It is hoped that this research can contribute to the development of interesting and interactive learning methods, as well as assist teachers in teaching and improve students' ability to listen and understand stories.